MRI versus mammography for breast cancer screening in women with familial risk (FaMRIsc): a multicentre, randomised, controlled trial. Issue 8 (August 2019) - Saadatmand, Sepideh; Geuzinge, H Amarens; Rutgers, Emiel J T; Mann, Ritse M; de Roy van Zuidewijn, Diderick B W; Zonderland, Harmien M; Tollenaar, Rob A E M; Lobbes, Marc B I; Ausems, Margreet G E M; van 't Riet, Martijne; Hooning, Maartje J; Mares-Engelberts, Ingeborg; et al.
Summary: Background: Approximately 15% of all breast cancers occur in women with a family history of breast cancer, but for whom no causative hereditary gene mutation has been found. Screening guidelines for women with familial risk of breast cancer differ between countries. We did a randomised controlled trial (FaMRIsc) to compare MRI screening with mammography in women with familial risk. Methods: In this multicentre, randomised, controlled trial done in 12 hospitals in the Netherlands, women were eligible to participate if they were aged 30–55 years and had a cumulative lifetime breast cancer risk of at least 20% because of a familial predisposition, but were BRCA1, BRCA2, and TP53 wild-type. Participants who were breast-feeding, pregnant, had a previous breast cancer screen, or had a previous a diagnosis of ductal carcinoma in situ were eligible, but those with a previously diagnosed invasive carcinoma were excluded. Participants were randomly allocated (1:1) to receive either annual MRI and clinical breast examination plus biennial mammography (MRI group) or annual mammography and clinical breast examination (mammography group). Randomisation was done via a web-based system and stratified by centre. Women who did not provide consent for randomisation could give consent for registration if they followed either the mammography group protocol or the MRI group protocol in a joint decision with their physician. Results from the registration group were only used in the analyses stratified by breast density. Primary outcomes were number, size, and nodal status of detected breast cancers. Analyses were done by intention to treat. This trial is registered with the Netherlands Trial Register, number NL2661. Findings: Between Jan 1, 2011, and Dec 31, 2017, 1355 women provided consent for randomisation and 231 for registration. 675 of 1355 women were randomly allocated to the MRI group and 680 to the mammography group. 218 of 231 women opting to be in a registration group were in the mammography registration group and 13 were in the MRI registration group. The mean number of screening rounds per woman was 4·3 (SD 1·76). More breast cancers were detected in the MRI group than in the mammography group (40 vs 15; p=0·0017). Invasive cancers (24 in the MRI group and eight in the mammography group) were smaller in the MRI group than in the mammography group (median size 9 mm [5–14] vs 17 mm [13–22]; p=0·010) and less frequently node positive (four [17%] of 24 vs five [63%] of eight; p=0·023). Tumour stages of the cancers detected at incident rounds were significantly earlier in the MRI group (12 [48%] of 25 in the MRI group vs one [7%] of 15 in the mammography group were stage T1a and T1b cancers; one (4%) of 25 in the MRI group and two (13%) of 15 in the mammography group were stage T2 or higher; p=0·035) and node-positive tumours were less frequent (two [11%] of 18 in the MRI group vs five [63%] of eight in the mammography group; p=0·014). All seven tumours stage T2 or higher were in the two highest breast density categories (breast imaging reporting and data system categories C and D; p=0·0077) One patient died from breast cancer during follow-up (mammography registration group). Interpretation: MRI screening detected cancers at an earlier stage than mammography. The lower number of late-stage cancers identified in incident rounds might reduce the use of adjuvant chemotherapy and decrease breast cancer-related mortality. However, the advantages of the MRI screening approach might be at the cost of more false-positive results, especially at high breast density. Funding: Dutch Government ZonMw, Dutch Cancer Society, A Sister's Hope, Pink Ribbon, Stichting Coolsingel, J&T Rijke Stichting.